Health-Related Quality of Life of Omani Colorectal Cancer Survivors. (8th March 2022) - Al-Shandudi, Maryam; Al-Mandhari, Mansour; Chan, Moon Fai; Al-Hajri, Thuraiya; Al-Balushi, Muna; Al-Azri, Mohammed
Background: Colorectal cancer (CRC) patients often experience physical and psychological symptoms which affect quality of life (QOL). Purpose: This study aimed to identify factors affecting QOL among adult Omani CRC survivors. Methods: A prospective cross-sectional study of 124 adult CRC survivors was conducted at the two main oncology referral hospitals in Oman. A validated Arabic version of the European Organisation for Research and Treatment of Cancer-Quality of Life Questionnaire for Colorectal Cancer-29 (EORTC QLQ-CR29) was used to collect data. Results: Of the 118 participants (response rate: 95.2%), 59 (50.0%) were male. The mean age was 52.7 years. Overall, 102 (86.4%) had been diagnosed with CRC at stages II or III. High mean scores on the QLQ-CR29 functional scale were reported for body image (88.9), weight (79.3), and anxiety (75.4). Mean scores for sexual interest were lower in men (31.4) compared to women (62.2). Severe anxiety was reported in 12 survivors (10.2%). Age, gender, the presence of comorbidities, and tumor location were significant predictors of QOL ( P ≤ .05). Conclusion: Omani CRC survivors demonstrated satisfactory QOL, although men reported more anxiety and sexual problems. Healthcare providers in Oman should conduct regular assessments of CRC survivors and offer counseling services if necessary.